Preliminary checklist of marine mollusks from Beyt Dwarka, Gulf Of Kutch (eco-sensitive zone), Gujarat, India - Soni, Hiren B; Thakur, Kavita (International Journal of Environment, 2015)
Correction: On 05/06/2016 The spelling of the first author's name was changed from "Biren B Soni" to "Hiren B Soni". The preliminary investigation of marine mollusks of Beyt Dwarka was carried out to prepare a checklist at the island of Beyt Dwarka, Gulf of Kachchh (Eco-sensitive Zone), Okhamandal Taluka, Jamnagar District, Gujarat, India. The rapid ecological assessment revealed the occurrence of 82 species of mollusks, belonging to 61 genera, 32 families, 9 orders, and 3 classes (including uncommon / rare species). Of the reported species, Class Bivalvia was represented by 5 orders, 8 families, and 20 species, followed by 4 orders of Gastropoda distributed in 23 families and 60 species, and only 1 order (Scaphopoda) with 1 family and 2 species. Of 82 species, 67 species were common throughout the study period (October 2013 to February 2014), whereas 15 species were designated as uncommon or rare therein. The overall ratio of Order, Family and Species of recorded molluscan taxa was found to be 3.00: 3.56: 2.56. From the present survey, it was observed that the study area (Beyt Dwarka) is endowed with rich diversity of marine mollusks prevailed therein. Therefore, it should be declared as “Sanctum sanctorum” by employing grassroots efforts involving local inhabitants with the help of forest officials suggesting site-specific conservation and management strategies. International Journal of Environment Vol.4(2) 2015: 243-255